Nutritious - Based Product Idea Blueprint / Amirul Fareez Amir Khan...[et.al] - Amir Khan, Amirul Fareez; Osman, Mohd Firzuan; Sakir, Muhammad Safwat Sahal; Kamarudin, Azlan (Faculty of Plantation and Agrotechnology, 2016)
Our plan is to create new source of food to livestock while maintaining Good Agricultural Practices (GAP). Before the creating of agro-waste livestock food, we use corn and soybean as pellet to livestock. But after considering that in oil palm industry, waste from oil palm frond and kernel is let to be burned or decomposed, we come to new resolution; to reuse the waste as food product. To promote sustain agricultural environment, we carne out with our product the Palm Kernel Cake Pellet. From past research done by MPOB, kernel waste contain high protein that is good to livestock. In addition, for milk producing livestock such as cow and sheep, protein contain in kernel can also enhance protein in their milk. Another benefit of our product is Effective Organism (EM) that can enhance good digestion of livestock. EM acts as good bacteria to make livestock intestine circulate well. After our long discussion and research, we have come out to open our Agrowaste Enterprise to compete with other livestock producer. Although there are a lot of the competitors, we very sure that our product can make hit in the market as we provide additional benefit to our product; the EM and kernel waste. In order to achieve this, we work as a team to achieve our goal while applying GAP. So as the General Manager of the company, I Amirul Fareez Bin Amir Khan would like to encourage my executive member and staff to join me to strive in order to achieve our mission.